Microbiota and Tuberculosis: A Potential Role of Probiotics, and Postbiotics - Yue Liu; Yue Liu; Jiaqi Wang; Jiaqi Wang; Changxin Wu; Changxin Wu (Frontiers in Nutrition, 2021)
Tuberculosis (TB), caused by Mycobacterium tuberculosis attacking the lungs and other organs, is one of the most common infectious disease worldwide. According to the WHO's 2020 report, a quarter of the world's population were infected with M. tuberculosis, and ~1.4 million people died of TB. Therefore, TB is a significant public health concern, which requires cost-effective strategies for prevention and treatment. The microbiota has been considered as a “forgotten organ” and a complex dynamic ecosystem, which plays a significant role in many physiological processes, and its dysbiosis is closely associated with infectious disease. Recently, a few studies have indicated associations between TB and microbiota. This review summarizes studies concerning the alterations of the gut and respiratory microbiota in TB, and their relationship with host susceptibility to M. tuberculosis infection, indicating that microbiota signatures in different stages in TB progression could be considered as biomarkers for TB diagnosis and control. In addition, the potential role of probiotics and postbiotics in TB treatment was discussed.